2021
DOI: 10.1371/journal.pone.0248769
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sensory evaluation of spinach freshness using machine learning model and digital images

Abstract: The visual perception of freshness is an important factor considered by consumers in the purchase of fruits and vegetables. However, panel testing when evaluating food products is time consuming and expensive. Herein, the ability of an image processing-based, nondestructive technique to classify spinach freshness was evaluated. Images of spinach leaves were taken using a smartphone camera after different storage periods. Twelve sensory panels ranked spinach freshness into one of four levels using these images.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…However, the accuracy of the three-factor models was not significantly improved. These findings were similar to those of the previous studies that used machine learning models and digital images to predict fresh spinach stages [ 35 ]. The results of the present study showed that the more combination factors there were, the lower the accuracy of the model and the overall prediction effect.…”
Section: Discussionsupporting
confidence: 91%
“…However, the accuracy of the three-factor models was not significantly improved. These findings were similar to those of the previous studies that used machine learning models and digital images to predict fresh spinach stages [ 35 ]. The results of the present study showed that the more combination factors there were, the lower the accuracy of the model and the overall prediction effect.…”
Section: Discussionsupporting
confidence: 91%
“…The various kinds of electrochemical sensors used for e-nose are metal oxide gas sensors, fiber-optic gas sensors, etc. (Koyama et al, 2021;Miguel and Laura, 2009;Yakubu et al, 2021). Finally, the third element is the data analysis and processing system helping in interpretation of the data generated by the detection system (Tan et al, 2019).…”
Section: Elements Of Sensory Analytical Toolsmentioning
confidence: 99%
“…It deals with the visual inspection of quality characteristics of food products by capturing, processing, and analyzing images. Due to its cost-effectiveness, superior speed, accuracy, and consistency, e-eye has been successfully used for quality analysis of meat, fish, pizza, cheese, bread, and cereal grains (Koyama et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Though the freshness of food materials is prospective, it regulates the consumer preference most. Freshness depends on the variety of the fruit, and on the experience of the evaluator (Koyama et al 2021). Objective indices and consumer evaluation has been combined to follow the freshness concept in terms of consumer perception (Koyama et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Freshness depends on the variety of the fruit, and on the experience of the evaluator (Koyama et al 2021). Objective indices and consumer evaluation has been combined to follow the freshness concept in terms of consumer perception (Koyama et al 2021). Quantifiable standards like colour, texture and shape perform as a critical indicator during interpretation of sensory evaluation.…”
Section: Introductionmentioning
confidence: 99%